Increased Market Transparency in Germany's Gasoline Market What about Rockets and Feathers?. (1st April 2020) - Frondel, Manuel; Horvath, Marco; Vance, Colin; Kihm, Alexander
Drawing on panel data on daily fuel prices covering more than 5, 000 filling stations in Germany, this paper documents a change in the stations' price-setting behaviour following the introduction of a legally mandated online price portal in 2013. Prior to the portal, positive asymmetry is found on the basis of error correction models, with prices following the 'rockets and feathers' pattern typically found for fuels. In the aftermath of the portal, negative asymmetry is observed: fuel price decreases in response to refinery price decreases are stronger than fuel price increases due to refinery price increases. This reversal in price pass-through, suggests welfare gains for consumers from increased market transparency.